PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS TINGGI PADA MATA PELAJARAN MATEMATIKA DI SD N 44 PADANG MARDANI - nita, Oknita; Arifin, Slamet; Fatimah, Fatia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This critical thinking ability is very useful in the learning process of students in each lesson, including in mathematics. This study aims to determine how much influence motivation and discipline have on the critical thinking ability of high-class students in mathematics at SD N 44 Padang Mardani. The results of data analysis show that; (1) motivation has a positive and significant effect on students' critical thinking ability, this is indicated by a coefficient value of 0.379 with a t count of 3.975 and a significance of (0.000) < α (0.05); (2) discipline has a positive and significant effect on students' critical thinking skills, this is indicated by a coefficient value of 0.330 with a t count of 2.505 and a significance of (0.000) < α (0.05). (3) motivation and discipline together have a positive and significant effect on students' critical thinking skills. F count of 10.618 and Sig of 0.000. Sig (0.000) < Alpha (0.05). Based on the results of the study, it can be concluded that there is an influence of motivation and discipline on the critical thinking skills of high-class students in mathematics at SD N 44 Padang Mardani.